PENERAPAN STRATEGI BAURAN PEMASARAN USAHA PADA WINGKO BABAT PAK SUGITO DI MERBAU - BANYUMANIK - Dina Kharisma; Evi Evi (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Abstract : UMKM are one of the important pillars in the national economic sector. UMKM need to be boosted again after the Covid-19 pandemic. One of the things that can be done to encourage the rise of UMKM is by digitizing marketing. The more workers, the greater the number of jobs created. So that UMKM, workers can return to normal and the economy starts to improve. This study aims to determine the marketing mix applied by Wingko Tripe producers. This study used descriptive analysis, interview and observation data collection techniques, and purposive sampling techniques. There are 3 samples in this study (respondents) who are business owners of Wingko Tripe, consumers, and the research team